2004
DOI: 10.1038/sj.cr.7290235
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of neurodegenerative disorders: How good are they?

Abstract: Biomarkers are very important indicators of normal and abnormal biological processes. Specific changes in pathologies, biochemistries and genetics can give us comprehensive information regarding the nature of any particular disease. A good biomarker should be precise and reliable, distinguishable between normal and interested disease, and differential between different diseases. It is believed that biomarkers have great potential in predicting chances for diseases, aiding in early diagnosis, and setting standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 82 publications
1
73
0
2
Order By: Relevance
“…37 Clinical studies demonstrated a reduction of SOD activity in Parkinsonism associated with other neurodegenerative disorders, showing the key role played by this enzyme in fighting free radicals produced in the brain. 38,39 In our results, we observed that in some tissues (cerebral cortex, hippocampus, liver, and plasma) CCl 4 decreased SOD activity. According to Chang et al, 40 the decrease of SOD activity by CCl 4 could result from the consumption of SOD to compensate excessive peroxyl radicals derived from CCl 4 's metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…37 Clinical studies demonstrated a reduction of SOD activity in Parkinsonism associated with other neurodegenerative disorders, showing the key role played by this enzyme in fighting free radicals produced in the brain. 38,39 In our results, we observed that in some tissues (cerebral cortex, hippocampus, liver, and plasma) CCl 4 decreased SOD activity. According to Chang et al, 40 the decrease of SOD activity by CCl 4 could result from the consumption of SOD to compensate excessive peroxyl radicals derived from CCl 4 's metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…Biomarkers are a subclass of endogenously occurring indicators, which signify the pathological state (Rachakonda et al 2004) 8 . An ideal biomarker is specific, sensitive, noninvasive, inexpensive, reproducible, suitable for large-scale population screening and readily available.…”
Section: Introductionmentioning
confidence: 99%
“…4 Biomarkers are of extreme relevance in chronic neurodegenerative diseases such as HD, since it is not possible to sample brain tissue to monitor pathophysiological processes. 5 Tremendous efforts have been made to identify neuropathological, biochemical and genetic biomarkers of these diseases, with the intention of establishing diagnosis earlier in the disease course to enable surveillance of the rate of progression and response to treatment. The mutation that encodes CAG expansion is a definitive diagnostic marker for HD, but provides no information on the clinical progression of HD.…”
Section: Introductionmentioning
confidence: 99%